Analisis Implementasi Model Pembelajaran berbasis Etnosains dalam Pembelajaran Tematik di Madrasah Ibtidaiyah - muh Thalaat; Wawan Mulyadi Purnama; Nishfiya Ramdoniati (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2022)
Ethnoscience Learning is one of the new breakthroughs in the world of education, which is collected between culture and science. Ethnoscience lifts local culture and wisdom to be usend as learning object to make the learning become more meaningful. The aimed of this research was to analyze the application of ethnographic based learning model, so the teacher could improve the quality of thematic learning in elementary school by understanding the learning resources that could be used in learning and the used of method in d elivering the material. The sampling technique was done by purposive sampling, with a sample of three elementary schools in Lenek District, Lombok Timur. Data were collected through interviews, documentation, literature studies, and analyzed by using descriptive qualitative. Based on the results of data analysis and discussion, it ccould be concluded that: 1) the planning application of Ethnoscience based learning models in three elementary school in Lenek District, Lombok Timur was unplanned well but the school has unconsciously implemented Ethnoscince, the application of Ethnoscience had been run well because it was proven by the teacher who had been being able to determine the local wisdom and sorted the material that would be integrated in thematic Ethnos cince subject based on local wisdom, and in the evaluation process there was an evaluation in accordance with the evaluation standard in curriculum 2013, namely : cognitive, affective, and psychomotor. 2) The used of learning resources was not maximal in ethnoscience learning because the teachers could utilize other learning resources such as the surrounding environment, video, and the internet. 3) Teachers ccould use various methods such as observation, demonstration, discussion, projects, experiments, and field trips.